Tinjauan Yuridis Sengketa Pembagian Harta Bersama Setelah Perceraian (Studi Kasus di Pengadilan Agama Salatiga) - H.Omy, Syahrul Basyar Bin (2017)
The purpose of this study was to determine the acquired rights of husband and wife respectively of the joint property after divorce according to Islamic law, customary law, civil law the west, as well as consideration of the judge in the division of joint property after divorce ruling stated. This research includes normative legal research. Research conducted at the District Court Salatiga. Source data using secondary data in the form of a ruling. Data were analyzed using qualitative analysis. The results showed that: 1) The division of joint property upon divorce under Islamic law based on Article 96 and 97 KHI that each husband and wife got half of the joint property. Under customary law in Salatiga who embrace Parental kinship system, then the system of descent drawn along the lines of the old, or the lines of the two sides of the father and mother. In the event of dispute settlement through the Village Head Office. According to the civil law is divided equally over the husband and wife or between their heirs. 2) Consideration of the use of judges in determining the division of joint property decision is referring to the evidence and witnesses presented by the applicant party, while the Defendant did not submit evidence and witnesses. Furthermore, property acquired during the marriage become community property, so that at the time of divorce joint property is divided equally between the former husband and wife. Thus even in the case Number 1053 / Pdt.G / 2012 / PA.Sal division of joint property is no longer needed because each party agreed to give it to their children. Keywords: joint property after divorce, consideration of the judge